Causal analysis of education attainment and brain structure in chronic obstructive pulmonary disease: a Mendelian randomization study - Shaochu Zheng; Xiaotong Liu; Jinliang Kong; Jing Luo (The Egyptian Journal of Bronchology)
Abstract Background In recent years, multiple observational studies have confirmed the association between educational attainment and the incidence of chronic obstructive pulmonary disease (COPD). At the same time, advancements in neuroimaging have revealed changes in brain structure and function in COPD patients. However, due to the inherent limitations of traditional observational studies, these associations may be biased. Methods First, we performed a two-sample Mendelian randomization (MR) analysis to investigate the relationship between educational attainment and COPD. Second, we conducted a multivariable MR (MV-MR) analysis with educational attainment, lung function, smoking habits, and α1-antitrypsin levels as exposure factors for COPD. Then, we performed two-sample MR analyses between 3935 imaging-derived phenotypes (IDPs) and COPD, as well as between educational attainment and the IDPs. Finally, we calculated the proportion of the mediating effect of brain IDPs in the causal relationship between education and COPD. Results The two-sample MR analysis suggested that educational attainment was negatively associated with COPD (OR = 0.40; 95% CI, 0.29–0.55; P < 0.05). The MV-MR analysis indicated that the genetically predicted effect of education on COPD persisted even after adjusting for smoking history, lung function, and α1-antitrypsin levels (OR = 0.52; 95% CI, 0.33–0.83; P < 0.05). A total of 114 brain IDPs were found to have a causal relationship with COPD. Mediation analysis identified four IDPs that could serve as mediators in the causal relationship between education and COPD, with a mediation effect ratio of 1–5%. Conclusion Our findings support the protective causal effect of educational attainment on COPD risk and suggest that changes in some IDPs partially mediate the relationship between education and COPD. This indicates that observing changes in IDPs among individuals with lower educational attainment may help predict COPD risk and has significant implications for COPD prevention.